Mercado de créditos de recicláveis sob a perspectiva da gestão de resíduos urbanos e sua importância para o desenvolvimento da economia circular - Araujo, Cristiane Martinez Cortada de (2023)
The absence of an effective solid urban waste management affects the formation of smart cities and public health systems. As a result of the National Solid Waste Policy (PNRS), regulated by law 12.305/2010, management tools such as selective collection and reverse logistics support the growth of a credit-based market. This study analyzes the role of reverse logistics credits for collector cooperatives and cleantechs to explore the functioning of waste management in the circular economy based on these credits. The research was guided by the question: "What is the scenario of the market for recyclable credits, based on solid waste management systems, from the perspective of Cleantechs and recycling cooperatives?" To answer this question, an integrative qualitative method derived from the methodological approach proposed by John W. Creswell was used. Exploratory qualitative field research was conducted using semi-structured questionnaires and open-ended interviews with responsible personnel from Cleantech credit management companies and cooperative administrators from Recycling Cooperatives, which allowed for a better exploration of the market and a better cross-checking of data based on experiences and experiences of managers and employees of the companies involved in the recyclables market within the circular economy. As a result, the growth of the credit market and its advantages and disadvantages from the perspective of interviewed cooperatives and Cleantech managers were observed. It is concluded that the credits resulting from this process have the role of supporting the development of the market.